Technological Learning in the Accumulation of Technological Capabilities: A Study of the Automotive Industry in Mexico - Hernandez, Blanca Cecilia Salazar; Moheno, Jessica Mendoza; Calzada, Martin Aubert Hernandez (European Scientific Journal, ESJ, 2017)
This paper will analyze the use of technological learning mechanisms in automotive industry companies located in the central part of Mexico -in the states of Guanajuato, Hidalgo and Queretaro. It will also analyze their impact in the accumulation of technological capabilities. It will explain which mechanisms were used according to the size of these companies. The analysis will conclude that micro-companies face serious limitations in this regard, while medium-size and large companies make better use of the different mechanisms for technological learning which can be seen in the innovation of these businesses.